The Effect of Octenidine on Proliferation, Migration, and Osteogenic Differentiation of Human Dental Pulp and Apical Papilla Stem Cells - Cassiano, Ana Flávia Balestrero [UNESP] (2022)
Introduction: The research for alternative irrigating solutions is ongoing, since no “ideal” solution has yet been found. Octenidine dihydrochloride (OCT) has been indicated as an endodontic irrigant because it has adequate antimicrobial and biological properties. The present study aimed to assess the effects of OCT on proliferation, migration, and induction of the osteogenic phenotype of stem cells from human dental pulp and apical papilla. Methods: Cells were collected from human third molars and exposed to different doses of OCT, chlorhexidine (CHX), sodium hypochlorite (NaOCl), and ethylenediaminetetraacetic acid (EDTA) to determine cell viability by alamarBlue assay; proliferation by bromodeoxyuridine incorporation; migration by the Transwell assay; alkaline phosphatase activity by thymolphthalein release; and production of mineralized nodules by alizarin red staining. The results were analyzed by 1- or 2-way analysis of variance and Tukey (α =.05). Results: CHX promoted lower cell viability, followed by OCT, NaOCl, and EDTA, especially at intermediate doses (P <.05). Cells exposed to CHX had less proliferation than the other groups (P <.05). The Transwell assay revealed no differences among OCT, EDTA, and culture medium (control group) (P >.05). OCT and EDTA induced greater migration than CHX and NaOCl (P <.05). OCT and EDTA induced higher alkaline phosphatase activity than NaOCl and CHX (P <.05). No difference was detected among the groups using alizarin red staining (P >.05). Conclusions: OCT induced high migration, proliferation, and alkaline phosphatase activity of stem cells from human dental pulp and apical papilla, which could be advantageous for regenerative endodontic procedures.